Handbook of Surface Plasmon Resonance 2017
DOI: 10.1039/9781788010283-00149
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Kinetic Binding Traces with Distributions of Surface Sites

Abstract: In kinetic surface binding experiments, deviations from the ideal exponential binding traces are commonly observed. Often, these can be attributed to the intrinsic heterogeneity of the binding properties of the immobilized molecules. Surface binding traces can be fitted with a mathematical model consisting of a heterogeneous distribution of surface sites with quasi-continuous affinity constants and kinetic rate constants. It is implemented in the software EVILFIT both for reaction-controlled binding and, if re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The determined K D2 value (112.310 nM; Figure 4B) is comparable with the dissociation constant revealed in solution by microscale thermophoresis (134.6 nM) (Sonnleitner et al, 2018). The best fitted binding kinetic for the Hfq/amiE 6ARN /Crc complex deviated from the ideal 1:1 kinetic, which is often observed in surface binding experiments and mainly due to mass transport limitations or heterogeneity of the surface/binding sites (Schuck and Zhao, 2010;Zhao and Schuck, 2017). As Crc is immobilized on the surface, it is possible that not all interaction sites were available for multivalent binding of Crc to Hfq/amiE 6ARN (Pei et al, 2019), which might explain the observed heterogeneous binding affinities.…”
Section: Catabolite Repression Control Protein Antagonist Interacts W...supporting
confidence: 73%
“…The determined K D2 value (112.310 nM; Figure 4B) is comparable with the dissociation constant revealed in solution by microscale thermophoresis (134.6 nM) (Sonnleitner et al, 2018). The best fitted binding kinetic for the Hfq/amiE 6ARN /Crc complex deviated from the ideal 1:1 kinetic, which is often observed in surface binding experiments and mainly due to mass transport limitations or heterogeneity of the surface/binding sites (Schuck and Zhao, 2010;Zhao and Schuck, 2017). As Crc is immobilized on the surface, it is possible that not all interaction sites were available for multivalent binding of Crc to Hfq/amiE 6ARN (Pei et al, 2019), which might explain the observed heterogeneous binding affinities.…”
Section: Catabolite Repression Control Protein Antagonist Interacts W...supporting
confidence: 73%
“…The pre-immobilized receptors can be divided into two portions, free receptors on the sensor chip surface (B) and receptors have already been combined with analytes (AB). The formation rate of AB can be expressed as [25,26].…”
Section: Pseudo First-order Reactionmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) has been demonstrated as a technique of choice for real-time determinations of binding affinity and kinetics between biologically important molecules. SPR has gained additional attention in the pharmaceutical industry, because it is viable for detecting binding of small molecules to purified proteins or receptors at cell membranes . Besides, SPR detection does not require the addition of an external or exogenous label to small molecules, which could significantly change the binding behavior.…”
mentioning
confidence: 99%